ANALISIS RESIKO EKONOMI PENGGUNAAN KAWASAN PADA RENCANA TATA RUANG WILAYAH (STUDI KASUS RISIKO EKONOMI PENGGUNAAN LAHAN DI PROVINSI KALIMANTAN TIMUR) - Abdul Rahmi; Zulkarnain Zulkarnain (RJABM (Research Journal of Accounting and Business Management), 2020)
This study aims to examine the economic risks of the negative impacts of some land usage and to determine magnitude of the economic risk caused by land use. This research was conducted for 4 (four) months in the GIS laboratory of the Faculty of Agriculture of Mulawarman University and several government agencies in the Province of East Kalimantan. This study used descriptive analysis method with an economic assessment of expenditures made to improve conditions for the use of the area on basis rules of regional ecosystem. The results showed that: (1) the economic risk of land use impacts is that state revenues from exploitation of natural resources are insufficient to make repairs to the damage that occurred and (2) the amount of economic risk caused by the use of mining land and forestry in the amount of Rp. 20.040.837.903.712.400,00 and Rp. 1.358.921.159.228.910,00